References to Philo of Alexandria in Greek, Latin, Syriac, and Arabic Literature up to 1500 CE - Runia, David T. (The studia Philonica annual, 2023)
In 1994 in the pages of this journal David Runia published a list of named references to Philo of Alexandria up to the year 1000 CE.¹ Based on research that he had done for his monograph on Philo in early Christian literature,² the list aimed at completeness in the case of Greek and Latin texts, which were placed together in approximately chronological order. A limited selection of references to Philo in Armenian and Syriac literature was added as well. In the past nearly three decades scholarship has not stood still. The present list is a greatly expanded version, using the...